Feasibility and implementation of community-based malaria case management with integrated vector control in the Democratic Republic of Congo. (December 2016) - Swana, Edouard; Makan, Ghislain; Mukeng, Clarence; Mupumba, Henriette; Kalaba, Gabriel; Luboya, Oscar; Bangs, Michael
Abstract Background Malaria prevalence in the Mulumbu Health Area in Lualaba Province, Democratic Republic of the Congo has remained high (>70 %) despite repeated vector control (indoor residual spray) and mass insecticide-treated bed net coverage. Therefore, a pilot study was implemented to attack the parasite directly and demonstrate the feasibility and acceptability of community case management of malaria (CCMm) using trained community health workers (CHWs). Methods A 13 month prospective evaluation of CCMm was undertaken in 14 rural villages. Focus group discussions and structured interviews were conducted in pre- and post-intervention periods to assess community acceptability of CCMm. Weekly data collected by CHWs assessed program impact over time, matched with malaria school-based prevalence surveys (MSPS) in the Mulumbu Health Area (CCMm study arm) compared to a comparison (non-CCMm) arm in the Mpala Health Area approximately 25 km apart. Results Overall population perception of the CCMm was highly positive. 6619 community contacts were managed by CHWs from which 1433 (21.6 %) were malaria positive by rapid detection tests during the 10 month intervention. Among the malaria infected, 94.7 % (1358) were recorded as 'uncomplicated' infections with 99.7 % provided full course of treatment. CHWs referred 278 (4.2 %) patients deemed 'complicated' to a designated primary health center for advanced care. While pre-intervention MSPS data revealed significantly higher (p = 0.0135) malaria in the CCMm area compared to the non-CCMm area, at post-intervention there was no statistical difference (p = 0.562) between the two areas. Notably, for the first time, no malaria-related deaths were recorded in the 14 CCMm intervention villages during observation. Conclusion Community case management of malaria was shown to be an effective and promising strategy for prompt and effective management of malaria. It was well accepted by the community and showed evidence of a reduction in malaria morbidity and mortality. Further refinement of CCMm implementation, cost implications and sustainability is advised before expanding the programme.